1992
DOI: 10.1103/physreva.45.197
|View full text |Cite
|
Sign up to set email alerts
|

Absolute total cross sections for the scattering of 2–18-eV electrons by cesium atoms

Abstract: Absolute total cross sections for the scattering of electrons by cesium atoms between 2 and 18 eV have been measured using the atomic-recoil technique in the scattering-out mode. Our results are somewhat lower than those of Visconti, Slevin, and Rubin [Phys. Rev. A 3, 131011971)]above 2 eV.PACS number(s): 34.80.i

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…Recent theoretical results using the CCC scheme reported by MacAskill et al [16] and Lukomski et al [17] covering our energy range, others in the low-energy range reported earlier by Karule and Peterkop [10], Burke and Mitchell [11], and the experimental results reported by Visconti et al [7], Jaduszliwer and Chan [8], Chen and Gallagher [19] and McFarland and Kinney [20], are shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Recent theoretical results using the CCC scheme reported by MacAskill et al [16] and Lukomski et al [17] covering our energy range, others in the low-energy range reported earlier by Karule and Peterkop [10], Burke and Mitchell [11], and the experimental results reported by Visconti et al [7], Jaduszliwer and Chan [8], Chen and Gallagher [19] and McFarland and Kinney [20], are shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 93%
“…The trap-loss rate γ e σ total (E 0 ) and the current density J(E 0 ) of the incident electron beam can be related according to the following equations: (8) where φ e is the flux of electrons with energy E 0 .…”
Section: Total Electron Impact Cross Section σ Total (E 0 )mentioning
confidence: 99%
See 1 more Smart Citation
“…A flexible bellows connecting the source assembly to the vacuum envelope allows us to align the source with the axis of the apparatus. The electron gun, described previously [9], is located at the center of the collision chamber; the interaction region, in which atomic and electron beams overlap, is centered 112 cm away from the oven outlet. The oven is operated normally with the cesium reservoir heated up to 200'C, and the outlet chamber about 25'C hotter.…”
Section: The Atomic-recoil Apparatusmentioning
confidence: 99%
“…The best choice of target atom for experimental studies of a situation in which both interactions are significant is cesium, which has a high atomic number Z, enhancing relativistic couplings, and is an alkali-metal atom, allowing for the simplest possible treatment of ex- We have built a spin-polarized cesium-beam apparatus to investigate the role of spin in electron-cesium collisions by the atomic-recoil technique [8] in which postcollisional observations are made on the recoiled atom, rather than on the scattered electron. This apparatus was used to measure electron-cesium total scattering cross sections [9], but since those measurements did not require a spinpolarized atomic beam, we did not discuss the apparatus features involved in beam-spin-state preparation and analysis. We spin-polarize the cesium atomic beam by optical pumping with Al-Ga-As diode lasers; our technique for state-sensitive detection of the atoms uses laser-induced fiuorescence in a magnetic field (LIFB).…”
Section: Introductionmentioning
confidence: 99%